Efektivitas Sistem Pembelajaran Jarak Jauh dalam Meningkatkan Literasi Teknologi Pendidikan Islam di Daerah Rural (Studi di Sarolangun) - Damanik, Jainab Rayanti; Jamrizal, Jamrizal; Yunus, Abdullah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid advancement of digital technology, accelerated by the COVID-19 pandemic, has significantly transformed educational systems worldwide, including Islamic education in rural areas. However, implementing distance learning (DL) in these settings presents unique challenges due to limited infrastructure, low digital literacy, and socioeconomic disparities. This study aims to evaluate the effectiveness of distance learning in enhancing technological literacy within Islamic education in rural Sarolangun, Indonesia. A qualitative approach was employed through a systematic literature review, focusing on scholarly works related to distance education, digital literacy, and Islamic pedagogy in rural contexts. Data were gathered from academic databases using keywords such as